(untitled) (Texas Journal of Medical Science, 2025)
Infertility is a concern to every reproductive age woman and their well-wishers and it’s on the increase across Africa. This raises concern among married women and their husband and is more rampant among both young and old in marriage. The aim of this study is to evaluate Rising Trend of Infertility Among Married women in the South-South. This was a descriptive study involving 350 female of reproductive age who were within the age of 18 to 47 years. A well-structured questionnaire was administered to participants. Each participant had one questionnaire to fill appropriately and independently after instructions were given to them by the Research Assistants. The study lasted for a period of 3 months. Exclusion criteria were those women that are not married, and are not up to reproductive age. Inclusion criteria are women that have done their investigations. Data was analyzed with SPSS version 26 and P value < 0.05 was considered significant. The results of the study shows that 42.9% of the respondents were within 28-32 years of age and 57.1% had tertiary education. The results revealed that 48.7% are business class, 71.4.7% are married, 71.4% yet to be pregnant, 42.9% have married between 2-4 years, 85.7% are been expecting baby, 71.3% do not have a child, 71.4% have breasts discharging milk, 90.0% had abortion, 77.1% have done investigations, and 87.5% of the participants were having infertility issues